Hacking the planet. (Economist, 2015)
The article discusses computer security and efforts to prevent computer hacking of computer integrated manufacturing systems. An overview of business enterprises in the Internet industries' efforts to prevent hacking, including the American multinational technology company Google's offering of monetary rewards to hackers who inform the company of its vulnerability to hacking, is provided.